Analisis Perhitungan Produk Domestik Regional Bruto (PDRB) Hijau Subsektor Tanaman Pangan dan Subsektor Perkebunan di Provinsi Kalimantan Selatan - Eryana, Maydati; Anshar Nur, Muhamad (PPJP ULM, 2025)
This research aims to analyze the magnitude of Depletion, Degradation, and Depreciation values in the Subsector of Food Crops and Plantation in South Kalimantan Province and analyze the magnitude of Green GRDP values in the Subsector of Food Crops and Plantation in South Kalimantan Province. This study is descriptive research utilizing quantitative data based on the Green GRDP concept, with secondary data as the source of information. From the result, it can be concluded that Conventional GRDP values tend to be higher that compared to calculations using the Green GRDP method.